The falling oil prices, effects in the colombian economy (2016)
The oíl sector in Colombia has been one of the main sources of economic development, both for transfers of funds from income that produces the nation and regions, such as the demand generated by its chain exploration and production. With the impact generated royalties to local authorities, equity and regional development is promoted through the distribution of resources to all departments. This paper explores the significant role played by oil in the country since the earliest historical records of its existence, the first explorations and concessions, shaping the sector, exploration stages of the business, and specifically analyzes the factors that have given rise to the fall in international prices and also the implications of the Colombian economy and the adoption of policies and fiscal measures of the national government to address the crisis.